2011
DOI: 10.1038/emboj.2011.336
|View full text |Cite
|
Sign up to set email alerts
|

Lateral assembly of the immunoglobulin protein SynCAM 1 controls its adhesive function and instructs synapse formation

Abstract: Synapses are specialized adhesion sites between neurons that are connected by protein complexes spanning the synaptic cleft. These trans-synaptic interactions can organize synapse formation, but their macromolecular properties and effects on synaptic morphology remain incompletely understood. Here, we demonstrate that the synaptic cell adhesion molecule SynCAM 1 self-assembles laterally via its extracellular, membrane-proximal immunoglobulin (Ig) domains 2 and 3. This cis oligomerization generates SynCAM oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 44 publications
7
74
0
1
Order By: Relevance
“…Thus, this work suggests that weaker preformed cis-dimers of TIGIT on the cell surface are required for cis-trans receptor oligomerization that is necessary for PVR signaling into primary cells. A similar coupling of cis-trans dimerization has been investigated for the covalent cishomodimers in the CTLA-4-B7-1/2 complexes and for noncovalent cis-homodimers in cadherins as well as in the CAR-JAML complex and the Necl-SynCAM2 (12,13,25,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this work suggests that weaker preformed cis-dimers of TIGIT on the cell surface are required for cis-trans receptor oligomerization that is necessary for PVR signaling into primary cells. A similar coupling of cis-trans dimerization has been investigated for the covalent cishomodimers in the CTLA-4-B7-1/2 complexes and for noncovalent cis-homodimers in cadherins as well as in the CAR-JAML complex and the Necl-SynCAM2 (12,13,25,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Several high-affinity homophilic trans-interactions have been described in detail for nectins/Necls and similar molecules (8)(9)(10)(11)(12)(13). However, the structure and function of the presumably weaker lateral homophilic cis-dimers in cell adhesion and their role in intracellular signaling is not known.…”
mentioning
confidence: 99%
“…In addition to the contribution of V-set domain in the dimer formation, previous cell biological studies indicated that the C-set domains of nectin or nectin-like molecules are involved in cis-interaction (Fig. 7A) (33)(34)(35). Related studies from different groups independently demonstrated that the C-set domains of nectin-2 and Necl-2 (SynCAM1) on the surface of the cells are responsible for the lateral clustering of the cis-interaction, which could complement or even promote the trans-interaction of these molecules (33,35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that nectins/Necls might form cisdimers through their first C-set domain and consequently form trans-dimers through their V-set domain during cell-cell adhesion (28,(33)(34)(35). This interactive mode of nectins/Necls may be supported by the structural determination of the Necl-1 (also known as synaptic CAM [SynCAM]3) V-set domain in 2006, in which the homodimer of Necl-1 was considered a trans-dimer (36).…”
mentioning
confidence: 99%
“…We added bis-sulfosuccinimidyl suberate (BS 3 ), an 11-Å -long cross-linker, to cells co-transfected with SynCAM1-HA and SynCAM1-Flag, and SynCAM1-HA and SynCAM2-Flag. Co-transfection of SynCAM1-HA and SynCAM1-Flag served as a positive control because SynCAM1 is known to form homophilic cis-complexes (Fogel et al, 2011). To make sure that trans-interactions did not confound our results, we re-plated transfected cells at low density.…”
Section: Syncams Form Homophilic and Heterophilic Cis-and Transinteramentioning
confidence: 99%